# How to plot the values found in a for loop?

13 views (last 30 days)
Nick Kavouris on 24 Sep 2020 at 16:27
Commented: David Hill on 24 Sep 2020 at 19:06
I have the following code
for g=((-3*pi())/2):0.1:0
Ebca=X*(Ex*cos((pi()/6)+g)^2+Ey*sin((pi()/6)+g)^2+Gamxy*sin((pi()/6)+g)*cos((pi()/6)+g))
Ebcb=Ex*cos(-(pi()/6)+g)^2+Ey*sin(-(pi()/6)+g)^2+Gamxy*sin(-(pi()/6)+g)*cos(-(pi()/6)+g);
Ebcc=Ex*cos((pi()/2)+g)^2+Ey*sin((pi()/2)+g)^2+Gamxy*sin((pi()/2)+g)*cos((pi()/2)+g);
end
I need to plot each Ebca, Ebcb, Ebcc value found in the loop with respect to g, how would i do this?
I know i need to create an array with the values found for each function with each value of g but I do no know how to do this.

David Hill on 24 Sep 2020 at 16:35
Are X, Ex, Ey, Gamxy constants not listed? Recommned executing without loop; otherwise you need to index Ebca/Ebcb/Ebcc. Currently you are overriding them during each loop execution.
g=-3*pi/2:0.1:0
Ebca=X*(Ex*cos((pi/6)+g).^2+Ey*sin((pi/6)+g).^2+Gamxy*sin((pi/6)+g).*cos((pi/6)+g));
Ebcb=Ex*cos(-(pi/6)+g).^2+Ey*sin(-(pi/6)+g).^2+Gamxy*sin(-(pi/6)+g).*cos(-(pi/6)+g);
Ebcc=Ex*cos((pi/2)+g).^2+Ey*sin((pi/2)+g).^2+Gamxy*sin((pi/2)+g).*cos((pi/2)+g);
plot(g,Ebca,g,Ebcb,g,Ebcc);

Nick Kavouris on 24 Sep 2020 at 16:41
these constants were found in an earlier part of the code
Here is the full code to this part
%% Part E
for g=(pi()/3)
Eaa=Ex*cos((pi()/6)+g)^2+Ey*sin((pi()/6)+g)^2+Gamxy*sin((pi()/6)+g)*cos((pi()/6)+g);
Eab=Ex*cos(-(pi()/6)+g)^2+Ey*sin(-(pi()/6)+g)^2+Gamxy*sin(-(pi()/6)+g)*cos(-(pi()/6)+g);
Eac=Ex*cos((pi()/2)+g)^2+Ey*sin((pi()/2)+g)^2+Gamxy*sin((pi()/2)+g)*cos((pi()/2)+g);
end
for g=(-pi()/6)
Eba=Ex*cos((pi()/6)+g)^2+Ey*sin((pi()/6)+g)^2+Gamxy*sin((pi()/6)+g)*cos((pi()/6)+g);
Ebb=Ex*cos(-(pi()/6)+g)^2+Ey*sin(-(pi()/6)+g)^2+Gamxy*sin(-(pi()/6)+g)*cos(-(pi()/6)+g);
Ebc=Ex*cos((pi()/2)+g)^2+Ey*sin((pi()/2)+g)^2+Gamxy*sin((pi()/2)+g)*cos((pi()/2)+g);
end
for g=(pi()/2)
Eaba=Ex*cos((pi()/6)+g)^2+Ey*sin((pi()/6)+g)^2+Gamxy*sin((pi()/6)+g)*cos((pi()/6)+g);
Eabb=Ex*cos(-(pi()/6)+g)^2+Ey*sin(-(pi()/6)+g)^2+Gamxy*sin(-(pi()/6)+g)*cos(-(pi()/6)+g);
Eabc=Ex*cos((pi()/2)+g)^2+Ey*sin((pi()/2)+g)^2+Gamxy*sin((pi()/2)+g)*cos((pi()/2)+g);
end
g=((-3*pi())/2):0.1:0
Ebca=(Ex*cos((pi()/6)+g)^2+Ey*sin((pi()/6)+g)^2+Gamxy*sin((pi()/6)+g)*cos((pi()/6)+g));
Ebcb=Ex*cos(-(pi()/6)+g)^2+Ey*sin(-(pi()/6)+g)^2+Gamxy*sin(-(pi()/6)+g)*cos(-(pi()/6)+g);
Ebcc=Ex*cos((pi()/2)+g)^2+Ey*sin((pi()/2)+g)^2+Gamxy*sin((pi()/2)+g)*cos((pi()/2)+g);
Nick Kavouris on 24 Sep 2020 at 16:47
the code you provided me worked beautifully! thank you for the assistance
David Hill on 24 Sep 2020 at 19:06
If you get a change, please accept the answer to close the question.